A Gradient Projection Algorithm with a New Stepsize for Nonnegative Sparsity-Constrained Optimization. (26th August 2020) - Li, Ye; Sun, Jun; Qu, Biao
Abstract : Nonnegative sparsity-constrained optimization problem arises in many fields, such as the linear compressing sensing problem and the regularized logistic regression cost function. In this paper, we introduce a new stepsize rule and establish a gradient projection algorithm. We also obtain some convergence results under milder conditions.